IDENTIFIKASI MASALAH DAN HIPOTESA DALAM PENELITIAN ILMIAH - Fitriani, Pina; Hayadi, Bambang Herawan; saputra, Dicky wahyu; Tresna, Popy Wulandari; Samsuri, Samsuri; Ma’arif, Tubagus Mahar (STAI Darul Qalam Tangerang, 2026)
Problem identification and hypothesis formulation are crucial stages in scientific research that determine the direction and quality of research outcomes. This study aims to analyze the concept of problem identification and hypotheses and their relationship in the research process. The method used is a literature study with a descriptive qualitative approach. The results show that clear, specific, and empirically grounded problem identification leads to well-directed and testable hypotheses. Furthermore, hypotheses function as guidelines in data collection and analysis. Therefore, accuracy in problem formulation significantly determines the quality of hypotheses and overall research success.